Revitalisasi Bisnis UMKM di Desa Waluyo Melalui Inovasi Digital - Aziezy, Enrico; Pahlevi, Akbar; Ramadhan, Sandi; Saputra, Achmad Adi (Penerbit Widina, Widina Media Utama, 2024)
The management of SMEs in Waluyo Village focuses on economic improvement through the adoption of digital technology. We carried out a community service activity themed